Efficacy and Safety of Piroxicam Patch versus Piroxicam Cream in Patients with Lumbar Osteoarthritis - Alessandro, Allegrini; Loredana, Nuzzo; Daniele, Pavone; Andrea, Tavella-Scaringi; Daniela, Giangreco; Marco, Bucci; Elena, Toniato; Andrea, Mezzetti; Stefano, Martinotti; Sergio, Comuzio; Maurizio Di, Grigoli; Stefano, Bonani (Arzneimittelforschung, 2009)
In order to assess the efficacy and safety of a new patch containing 14 mg of Piroxicam (CAS 36322–90-4) 1%, applied once daily, in comparison with a reference marketed formulation, piroxicam 1% cream applied three times a day, placebo patch applied once daily, a randomized, placebo-controlled, parallel-group clinical trial was carried out by general practitioners in patients with lumbar osteoarthritis aged between 18 and 75 years. Pain during daily activities scored on a 100 mm visual analogue scale was the primary outcome measure. Other secondary outcome measures were pain on isometric contraction, on full passive motion, and on pressure, and functional disability. Statistical analysis was performed on the differences between the three groups in the intention-to-treat population (ITT).One hundred and eighty patients were enrolled. The available ITT population comprised 179 patients. The compliance was very good. Decrease in pain score during daily activities after the eight days of study treatment (at the final visit, Vf) was 42.2%, 41.7% and 25.8% in the piroxicam patch, piroxicam cream and placebo groups, respectively. The difference between the pain scores in two active treatments arms was not statistically sig-nificant at the Vf whereas the differences between the pain scores of two active treatment arms vs the placebo arm were statistically significant validating the study design.All efficacy measures improved during the study, for both the active treatment groups, and the results for the secondary efficacy variables were generally consistent with those concerning the main efficacy criterion.The difference between the two active treatments in pain during daily activities were statistically significant at the final visit; in fact the 95% CI of the difference between the mean of responder rate of the piroxicam patch and piroxicam cream was −18.3%, +24.4% indicating a trend of superiority of the piroxicam patch versus the cream (per-protocol analysis).The data obtained during the intermediate visit (V2, day 4) allow us to assess that the piroxicam patch was on average better than the piroxicam cream in terms of fast pain reduction (change from baseline:–29.1% for piroxicam patch in comparison to −24.6% for piroxicam cream). Moreover the piroxicam patch proved to be on average more effective than the piroxicam cream in terms of secondary efficacy endpoints. Safety was considered satisfactory in all groups.The piroxicam patch is effective in the treatment of lumbar osteoarthritis and has demonstrated to be well tolerated and it improves patients compliance. The piroxicam patch offers a comparable alternative to the marketed piroxicam cream for the treatment of lumbar osteoarthritis with the advantage of a better compliance with the once a day application of the patch compared to three daily applications for the piroxicam cream.
Keywords: CAS 36322–90-4; Lumbar osteoarthritis; Non-steroidal anti-inflammatory drug (NSAID), patch; Piroxicam, efficacy, safety